Genetic advance in grain yield and other traits in two tropical maize composites developed via reciprocal recurrent selection - Kolawole, A.O.; Menkir, A.; Blay, E.; Ofori, K.; Kling, J. (Wiley, 2018)
Assessment of genetic gain in two tropical maize (Zea mays L.) composites improved across years is critical in determining their future improvement and use as sources of inbred lines. Two genetically complementary tropical maize composites were subjected to four cycles of reciprocal recurrent selection (RRS) for grain yield, resistance to foliar diseases, and other desirable agronomic traits using a reciprocal S1 testcross evaluation scheme. The objectives of this study were to evaluate the effects of this selection scheme on: (i) the rate of genetic gain in grain yield and other traits, (ii) the changes in variance and heritability estimates, and (iii) changes in correlations between grain yield and other traits in the two tropical maize composites. One hundred S1 lines, each derived from the original (C0) and advanced (C4) cycles of the two composites, were crossed in pairs to form 100 C0 × C0 and 100 C4 × C4 testcrosses, which were evaluated along with 10 commercial hybrid checks in a replicated trial across eight environments in Nigeria. The observed genetic gain was 3.60% cycle−1 for grain yield. On average, the top 10 C4 × C4 testcrosses outyielded the commercial hybrids by 29% and had desirable agronomic traits and improved resistance to foliar diseases. The genetic variance estimates for C0 and C4 of each composite were significantly larger than zero for most traits. These results indicated that the RRS was effective in improving grain yield and other desirable agronomic traits without diminishing genetic variability that can be exploited for further improvement of the two tropical maize composites.